Severe Consequences of the Development of Periodontal Disease in the Example of Employees Working in Light Industrial Plants (Texas Journal of Medical Science, 2023)
The article provides information about employees working in light industry production factories and periodontal disease, its development, spread, as well as its serious consequences.